Evaluating safety in hyaluronic acid lip injections. Issue 12 (2nd December 2021) - Safran, Tyler; Swift, Arthur; Cotofana, Sebastian; Nikolis, Andreas
ABSTRACT: Introduction: Soft tissue filler augmentation has become increasingly popular due to its perceived ease and impressive results. Unfortunately, although the results are impressive, so are the reported complications. This article describes complications specific to peri-oral soft tissue filler injection and then discusses evidence-based, anatomic prevention and treatment guidelines. Areas Covered: The authors aimed at providing an overview of the complications associated with peri-oral soft tissue filler. Hyaluronic Acid (H.A) fillers may have devastating complications which are oft undisclosed or published. This narrative review aims to describe the various complications and provide preventative strategies. Expert opinion: Given the paucity of prospective, randomized clinical trials on the subject and in light of complication underreporting, the authors believe that efficacy and safety literature on the subject is lacking. Injectors must rely on the one strength which exists in the lip literature to date, that is anatomy. The basis of all successful injections is a mandatory understanding of normal as well as variations of vital structures in an area, combined with meticulous injection techniques, deposition of small aliquots of product and the ability to recognize unwanted adverse events early enough to act on them.